2019
DOI: 10.15252/embj.2019101597
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism‐induced oxidative stress and DNA damage selectively trigger genome instability in polyploid fungal cells

Abstract: Understanding how cellular activities impact genome stability is critical to multiple biological processes including tumorigenesis and reproductive biology. The fungal pathogen Candida albicans displays striking genome dynamics during its parasexual cycle as tetraploid cells, but not diploid cells, exhibit genome instability and reduce their ploidy when grown on a glucose‐rich “pre‐sporulation” medium. Here, we reveal that C. albicans tetraploid cells are metabolically hyperactive on this medium with higher ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 87 publications
(116 reference statements)
2
44
0
Order By: Relevance
“…We propose that the host environment is inherently stressful and drives genome instability in C. albicans similarly to stressinduced mutagenesis. There are several physiologically relevant stressors that elevate LOH rates in vitro, including high temperature and oxidative stress (17,41). Reactive oxygen species (ROS) production is an innate immune defense used to defend the host against invading pathogens (7,8), which inhibits growth by inducing DNA damage (42).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that the host environment is inherently stressful and drives genome instability in C. albicans similarly to stressinduced mutagenesis. There are several physiologically relevant stressors that elevate LOH rates in vitro, including high temperature and oxidative stress (17,41). Reactive oxygen species (ROS) production is an innate immune defense used to defend the host against invading pathogens (7,8), which inhibits growth by inducing DNA damage (42).…”
Section: Discussionmentioning
confidence: 99%
“…Conjugation of opaque a and α cells (heterothallic mating) generates tetraploid a/α cells that are less virulent and less competitive than diploid cells in a model of systemic infection [40]. Recent profiling studies revealed few transcriptional differences between C. albicans diploid and tetraploid cells [44], similar to the analysis of S. cerevisiae cells of differing ploidy [45,46].…”
Section: Mating Ploidy Shifts and Aneuploidymentioning
confidence: 87%
“…29 Aberrant oxidative regulation has been observed in various types of cancer cells. 30,31 Mounting evidence indicates that perturbation of oxidative homeostasis is involved in tumorigenesis. 32,33 However, the roles of antioxidant molecules in malignant cancers, especially liver cancer, are relatively unclear.…”
Section: Discussionmentioning
confidence: 99%